Pandemic as boundary condition in service to communication theory building. Issue 3 (3rd July 2022) - Holbert, R. Lance; Baik, Elizabeth S.; Tallapragada, Meghnaa; Hardy, Bruce W.; Tolan, Colleen M.; LaMarre, Heather L.
ABSTRACT: The coronavirus pandemic is a unique context that can allow researchers to address boundary conditions. This essay details four different types of boundary conditions and emphasizes they are not created equal. A review of pandemic-related research published in nine communication journals reveals a relative dearth of studies exploring moderation-based effects, with even fewer of the proposed conditional relationships stemming from pandemic-driven rationales. A series of pandemic-as-boundary condition arguments are offered for three theories or models used within the field's extant pandemic-related research. The proposed insights offered by a pandemic-as-boundary-condition approach are shown to be unique accompaniments to the field's dominant research agendas. The essay closes with a call for a more systematic approach to identifying, testing, and assessing boundary conditions .